Autism and education—international policy in small EU states: policy mapping in Malta, Cyprus, Luxembourg and Slovenia. (3rd September 2020) - van Kessel, Robin; Hrzic, Rok; Czabanowska, Katarzyna; Baranger, Aurélie; Azzopardi-Muscat, Natasha; Charambalous-Darden, Nefi; Brayne, Carol; Baron-Cohen, Simon; Roman-Urrestarazu, Andres
Abstract: Background: Special education provides an array of support that can advantageously meet special education needs (SEN) of children with autism. This report maps autism and SEN policies, and tension of international legislation in Malta, Cyprus, Luxembourg and Slovenia. Methods: A policy path analysis was performed using a scoping review as fundamental methodological framework. Results: Education for children with SEN developed from limited education towards segregation, and further to integration, and inclusion in mainstream education. International policy has greatly influenced the education systems under study. The rights to education and to have SEN addressed have been adopted in all countries. Inclusion is seen to be gradually incorporated by Malta, Cyprus and Luxembourg—closely following values of international documents through concise SEN policies. Slovenia's education system remains segregated, indicating potential tension. Conclusions: It appears that mainstream schools offer SEN services until no longer feasible for the child in the majority of investigated countries. Inclusion has become a guiding principle for most education systems under study. Finally, small states either commit to the implementation of inclusion or delay it and attempt to improve the education system for children with SEN in different ways.